2005
DOI: 10.1152/physrev.00004.2004
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and Pathophysiology of the Calcium Store in the Endoplasmic Reticulum of Neurons

Abstract: The endoplasmic reticulum (ER) is the largest single intracellular organelle, which is present in all types of nerve cells. The ER is an interconnected, internally continuous system of tubules and cisterns, which extends from the nuclear envelope to axons and presynaptic terminals, as well as to dendrites and dendritic spines. Ca(2+) release channels and Ca(2+) pumps residing in the ER membrane provide for its excitability. Regulated ER Ca(2+) release controls many neuronal functions, from plasmalemmal excitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
602
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 667 publications
(631 citation statements)
references
References 696 publications
12
602
1
7
Order By: Relevance
“…39,40 Recent studies have shown an involvement of ER stress and disturbed calcium homeostasis in AD. 11,39,41 Analyses of brain tissue from AD patients revealed alterations in calcium metabolism that are associated with the neurodegenerative process. Neurons containing NFT showed an increase in the levels of free and protein bound calcium compared with tangle free neuron.…”
Section: Er Stress and Admentioning
confidence: 99%
See 4 more Smart Citations
“…39,40 Recent studies have shown an involvement of ER stress and disturbed calcium homeostasis in AD. 11,39,41 Analyses of brain tissue from AD patients revealed alterations in calcium metabolism that are associated with the neurodegenerative process. Neurons containing NFT showed an increase in the levels of free and protein bound calcium compared with tangle free neuron.…”
Section: Er Stress and Admentioning
confidence: 99%
“…Neurons containing NFT showed an increase in the levels of free and protein bound calcium compared with tangle free neuron. 11,12,39 Changes in calcium may be early events in AD as shown in studies on transgenic mice expressing mutant forms of APP or PS proteins. 11,12,39 Whether elevated cell calcium is the cause or a consequence of the increase in Ab in AD remains to be investigated.…”
Section: Er Stress and Admentioning
confidence: 99%
See 3 more Smart Citations